Effects of Fire Regime on Nitrogen Distribution in Marshlands of the Sanjiang Plain (NE China) - Shengzhen Ji; Hongmei Zhao; Guoping Wang; Jinxin Cong; Guangxin Li; Dongxue Han; Chuanyu Gao (Fire)
Fire is a key ecological factor in marshes, significantly influencing the nitrogen (N) cycle. The impacts of different fire regimes on marshes have garnered increasing attention. This study aims to reveal the effects of fire regimes on N distribution in marshes. We conducted field experiments with fixed–point prescribed burning in typical Sanjiang Plain freshwater marshes, exploring the influences of various fire regimes on the distribution of N in marshes. We found that in the spring–burned plots, the soil ammonium (<semantics><msubsup>NH4+</msubsup>–N</semantics>) content increased by 318% with thrice–burned approaches compared to once–burned, and by 186% with thrice–burned compared to twice–burned. In the autumn–burned plots, <semantics><msubsup>NH4+</msubsup>–N</semantics> content increased by 168% and 190%, respectively. Similarly, the soil nitrate (<semantics><msubsup>NO3–</msubsup>–N</semantics>) content three years subsequent to burning increased by 29.1% compared to one year since burning, and by 5.96% compared to two years since burning in the spring–burned plots (73.8% and 32.9% increases, respectively, in the autumn–burned plots). The plant stem–N content of the autumn burns increased by 30.9%, 119%, and 89.1% compared to the spring burns after one, two, and three years since burning, respectively. Our results indicate that high fire–frequency promotes marsh N cycling within the span of three years. The marsh soil conversion of <semantics><msubsup>NH4+</msubsup>–N</semantics> to <semantics><msubsup>NO3–</msubsup>–N</semantics> was enhanced with increased time since burning. High fire–frequency promotes plant growth, exacerbating competition between plant populations, with this effect being more significant in autumn–burned plots than in spring–burned plots.